2019
DOI: 10.1108/ijoem-07-2018-0371
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of profitability of life and non-life insurance companies: evidence from Ecuador

Abstract: Purpose The purpose of this paper is is to identify the main determinants of insurance profitability on life and non-life segments to obtain which variables affect in each market of the Ecuadorian insurance sector. Design/methodology/approach The authors use a large panel data set with financial information from 2001 to 2017 and estimate the determinants through a panel corrected standard errors regression. Findings The authors found that net premiums, technical reserves, capital ratio and score efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 90 publications
0
15
0
1
Order By: Relevance
“…Applying the chosen model in the observed period, we have realised that the growth of market share has a positive impact on ROA (hypothesis 8), but it is not statistically significant. The results of Camino-Mogro & Bermúdez-Barrezueta (2019) which analysed the life and non-life insurance market of Ecuador in the period 2001-2017, showed that the life insurance market had a statistically significant negative effect on the profitability of insurance companies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Applying the chosen model in the observed period, we have realised that the growth of market share has a positive impact on ROA (hypothesis 8), but it is not statistically significant. The results of Camino-Mogro & Bermúdez-Barrezueta (2019) which analysed the life and non-life insurance market of Ecuador in the period 2001-2017, showed that the life insurance market had a statistically significant negative effect on the profitability of insurance companies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…studied on Indonesia, Abdeljawad et al. (2020) studied on insurance companies in Palestine, study evidence from Ecuador Camino‐Mogro and Bermúdez‐Barrezueta (2019), Derbali and Jamel (2018). who studied on Tunisia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Between 2009 and 2015, the study included data from 30 Ghanaian insurers. According to the findings, While “no premium, no cover” and capital minimum restrictions don't even have a substantial driving effect on profitability, the presence of these restrictions has assisted insurers mitigate the adverse impact of liquidity and underwriting risks on economic performance (Camino‐mogro & Bermúdez‐Barrezueta, 2019). This article aims to define the critical indicators of life and general insurance profitability to acquire which factors impact the Ecuador insurance industry in each sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the presence of works studying efficiency levels in the insurance industry in recent years (Camino-Mogro & Bermúdez-Barrezueta, 2019 ; Nguyen & Worthington, 2020 ), they do not further investigate the effect of technological change. In the light of previous results, showing a moderate efficiency in the industry and of recent technological innovations with the potential to change the industry (Eling & Lehmann, 2018 ), in particular in the country mostly affected by innovative technological applications in insurance [i.e.…”
Section: Literature Reviewmentioning
confidence: 99%